The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.2527/1991.6952033x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced blood flow to peripheral and core body tissues in sheep and cattle induced by endophyte-infected tall fescue

Abstract: Four wethers and 14 steers (environmentally heat stressed, 32 degrees C, 60% relative humidity) were evaluated for changes in blood flow induced by endophyte-infected tall fescue. Concentration of the ergopeptide ergovaline was used as an indicator of diet toxicity due to the endophytic fungus Acremonium coenophialum. Blood flow to specific tissues was measured using radiolabeled microspheres. Wethers received one of two dietary treatments for 30 d before determination of tissue blood flow: 1) a low-endophyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 10 publications
7
90
0
Order By: Relevance
“…The production of high concentrations of epoxy-janthitrems by AR37-infected ryegrass compared with low concentrations of lolitrem B by standard endophyte-infected ryegrass, and the lower severity of ryegrass staggers on AR37-infected ryegrass pastures, indicates that the epoxy-janthitrems are low potency tremorgens compared with lolitrem B, as described by Finch et al (2012). Ingestion of ergovaline, and ergot alkaloids in general, are known to exacerbate heat stress in livestock due to constricting blood flow and therefore reducing the ability of the animal to dissipate heat through the skin (Rhodes et al 1991). Fletcher et al (1999) reported that differences in animals' ability to handle heat stress could be detected without the use of the tunnel house for sheep grazing standard endophyte ryegrass at Lincoln when measured on hot days in the field in summer and autumn.…”
Section: Discussionmentioning
confidence: 94%
“…The production of high concentrations of epoxy-janthitrems by AR37-infected ryegrass compared with low concentrations of lolitrem B by standard endophyte-infected ryegrass, and the lower severity of ryegrass staggers on AR37-infected ryegrass pastures, indicates that the epoxy-janthitrems are low potency tremorgens compared with lolitrem B, as described by Finch et al (2012). Ingestion of ergovaline, and ergot alkaloids in general, are known to exacerbate heat stress in livestock due to constricting blood flow and therefore reducing the ability of the animal to dissipate heat through the skin (Rhodes et al 1991). Fletcher et al (1999) reported that differences in animals' ability to handle heat stress could be detected without the use of the tunnel house for sheep grazing standard endophyte ryegrass at Lincoln when measured on hot days in the field in summer and autumn.…”
Section: Discussionmentioning
confidence: 94%
“…Inclusion of the endophyte in fed diets has resulted in increased rectal temperature and respiratory rate. In this regard, the effects of the endophyte were investigated using temperature controlled rooms , Rhodes et al 1991, Osborn et al 1992, Aldrich et al 1993b, Cornell et al 1990). Calves consuming a toxic ryegrass-tall fescue hybrid at increased ambient temperatures had increased rectal temperatures, respiratory rates and depressed body weight gains compared to those fed a non-toxic hybrid ; however, at lower ambient temperatures there were no differences in respiratory rate and rectal temperatures.…”
Section: Animal Toxicosis-tall Fescuementioning
confidence: 99%
“…Earlier work (Steen et al 1979, Bond et al 1984 indicated the hematocrit was likely suppressed in cattle grazing E+ tall fescue. In contrast, circulating numbers of red blood cells were not reduced in cattle on endophyte containing diets (Rhodes et al 1991). Since Cu is related to red blood cell production, a Cu deficiency could alter red blood cell parameters.…”
Section: Response Criteriamentioning
confidence: 89%
“…Inclusion of the endophyte in fed diets has resulted in increased rectal temperature and respiratory rate. In this regard, the effects of the endophyte were investigated using temperature controlled rooms , Rhodes et al 1991, Osborn et al 1992, Aldrich et al 1993b, Cornell et al 1990). Calves consuming a toxic ryegrass-tall fescue hybrid at increased ambient temperatures had increased rectal temperatures, respiratory rates and depressed body weight gains compared to those fed a non-toxic hybrid ; however, at lower ambient temperatures there were no differences in respiratory rate and rectal temperatures.…”
Section: Discussionmentioning
confidence: 99%